Selected acoustical parameters of highway noise barriers. - National Cooperative Highway Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 1978)
"An NCHRP staff digest of the essential findings from the final report on NCHRP Project 3-26, "Investigation of Selected Noise Barrier Acoustical Parameters," by S. I. Hayek, J. M. Lawther, R. P. Kendig, and K. T. Simowitz, The Pennsylvania State University, University PArk, Pa."
Caption title.
At head of title: National Cooperative Highway Research Program.
September 1978.
Keywords: Highway research -- United States